THE DEVELOPMENT OF YE. N. IVANOVA’S IDEAS OF THE SOIL GENESIS IN THE REPUBLIC OF KOMI - E. M. Lapteva; Ye. V. Shamrikova (Бюллетень Почвенного института им. В.В. Докучаева, 2014)
The paper is devoted to Yeugenia Nikolaevna Ivanova, an out-standing soil scientist and a founder of soil studies in the Republic of Komi. A brief review of the latest successes achieved by special-ists of the Institute of Biology in the Republic of Komi shows the development of Ye.N. Ivanova’s ideas presented in the publication entitled “Principal Regularities of the Soil Cover along the North-Pechora Railway” (1952).